CHECKLIST OF SPIDERS (ARACHNIDA ARANEAE) FROM CHAMPANER PAVAGADH ARCHAEOLOGICAL PARK, GUJARAT - YADAV, ARCHANA; KUMAR, DOLLY (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Spiders are one of the most diverse organisms in the terrestrial ecosystem and occupy the seventh position in global diversity. They are arthropods belonging to the class Arachnida and the order Araneae. Spiders are chiefly entomophagous, ubiquitous, harmless and biocontrol agents. The present study was conducted to document spider diversity in Champaner- Pavagadh Archaeological Park; a world heritage site in Gujarat, India. The spider fauna of this site has never been studied in its entirety despite contributions by many arachnologists in Gujarat. Spiders were collected by using active searching, pitfall, and sweep net methods. The study was conducted from January 2016 to December 2019. In the present research work, we compiled a checklist of spiders from Champaner-Pavagadh, Archaeological Park of Gujarat, India based on their taxonomic identification. A total of 189 species belonging to 106 genera and 32 families were collected during the study. The most dominant families reported were Salticidae followed by Araneidae, Lycosidae, and Theridiidae; Oxyopidae and Thomisidae. Finding twenty-seven new records of spiders is the highlight of this work